Penerapan Konsep Teori Model Cheryl Tatano Beck Pada Asuhan Keperawatan Depresi Postpartum - Hindri Royiah Fatma; Irna Nursanti (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
The studies that Beck used in developing the theory of postpartum depression led to qualitative methods, Beck also cited various philosophical and theoretical sources to develop his knowledge. The phenomenon used in the first study was how women experience postpartum depression, using the Colaizzi (1978) approach. Furthermore, Beck used the theoretical basis of the philosophical and theoretical views of Glaser (1978), Glaser and Strauss (1967), and Hutchinson (1986), all of whom made important contributions to the evolution of basic nursing theory. Through the results of Beck's study and its consistency with feminist theory. The results of his study concluded the importance of understanding pregnancy, the birth process, and the process of raising children according to women's views (Beck, 2002). In addition, the results of Beck's study concluded that the birth process has a sustainable impact in the context (medical, social, economic) and a mother's reactions to that process and the process of parenting is shaped by those responses.